2013
DOI: 10.1111/jpn.12090
|View full text |Cite
|
Sign up to set email alerts
|

Comparative digestibility of low‐quality grass hay by two breeds of cattle differing in mature live weight

Abstract: The digestive capacity of the Portuguese native breed of Barrosão cattle and the Holstein-Friesian breed was measured when fed meadow hay (72-74 g CP and 641-671 g NDF/kg dry matter), offered either alone or supplemented with soya bean meal (150 g/kg dry matter), at maintenance level. Four mature cows of each breed were used. Average initial live weight (LW) was 457 and 635 kg for the Barrosão and the Holstein-Friesian cows respectively. The organic matter digestibility (OMD) of the meadow hay was higher in Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In contrast to other studies that almost exclusively examined Holstein-Friesian calves, in this study Simmental calves were used, as this is the predominant dairy breed in the Alpine region (Klein-Jöbstl et al, 2014 ) and almost nothing is known about the microbiota of this breed. Studies examining different breeds in regard to feed and nutrient intake as well as digestibility of feed recognized breed differences (Jenkins and Ferrell, 2007 ; Fry et al, 2013 ; Gruber et al, 2014 ; Lourenço et al, 2014 ). Furthermore, not only the breed but also management and particularly feeding in our study differed from other studies (Uyeno et al, 2010 ; Edrington et al, 2012 ; Oikonomou et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies that almost exclusively examined Holstein-Friesian calves, in this study Simmental calves were used, as this is the predominant dairy breed in the Alpine region (Klein-Jöbstl et al, 2014 ) and almost nothing is known about the microbiota of this breed. Studies examining different breeds in regard to feed and nutrient intake as well as digestibility of feed recognized breed differences (Jenkins and Ferrell, 2007 ; Fry et al, 2013 ; Gruber et al, 2014 ; Lourenço et al, 2014 ). Furthermore, not only the breed but also management and particularly feeding in our study differed from other studies (Uyeno et al, 2010 ; Edrington et al, 2012 ; Oikonomou et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in mountain conditions, where a delayed first cutting is commonly adopted by all farmers [9]. Furthermore, fibrous feeds produced under these conditions are not only profitable for local breeds of cattle but also have potential in genetically improved breeds [27].…”
Section: Introductionmentioning
confidence: 99%
“…Lourenço et al. () observed a lower TTAD in a Portuguese native cattle breed (Barrosã) than in Holstein‐Frisian cattle. Comparing a Portuguese native sheep breed (Churra da Terra Quente) with the Ile‐France breed, Lourenço, Cone, Fontes, and Dias‐da‐Silva () observed a higher intake per kg BW and lower a TTAD in adult and in growing ewes (Lourenço, Dias‐da‐Silva, Fonseca, & Azevedo, ) of the native breed and demonstrated that this breed has an inherit higher outflow rate.…”
Section: Discussionmentioning
confidence: 98%